O ator da enunciação Sergio Moro: uma análise semiótica da trajetória de juiz a senador - Silva, Rafaela Aparecida da (Universidade Federal de São Carlos, 2024)
Discourse plays an important role in establishing different forms of power — this is even more evident due to the person’s social role. It is also through speeches that we can position ourselves ideologically, for or against certain issues and values. Based on these observations, this master's work presents an analysis, based on semiotics of Greimasian origin, of Sergio Moro's ethos, seeking to describe its main features and how it is constructed. For this, the corpus is formed from Lula's conviction sentence, when Sergio Moro was a judge, and also from interviews and statements given by him as a minister and senator, that is, as an outspoken politician. We seek to verify, by comparing these different data, transformations and continuities in relation to the production of ethos. The research is based, above all, on the reflections of José Luiz Fiorin (1996) and Norma Discini de Campos (2003) on enunciation and ethos, and dialogues with the works of Benveniste (1995) and Dominique Maingueneau (1995).
Sergio Moro, the actor of enunciation: a semiotic analysis of his trajectory from judge to senator
Keywords: Enunciação; Ethos; Semiótica; Paixões; Política; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; 8. Trabalho Decente e Crescimento Econômico